Decolonizing the Ethics of Intellectual Freedom: Exploring a New Intersectional Framework for Allyship and Ethical Practice - Ballantyne, Erin (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
The intersection between Indigenous allyship, intellectual freedom, and social responsibility is understudied in LIS literature. This conceptual paper employs literature-based critical analysis to explore the tension between these concepts and torwards the theoretical basis for a new interdisciplinary model for ethical information practice. The model draws on foundational aspects of human rights scholarship, human resources literature, philosophy, and uncertainty as a critical tradition for librarianship.